An absence of saints - Licari, Rosanna (Arts Queensland Thomas Shapcott Poetry Prize series., 2010)
A circle of vermillion flares into petals of yellow and white. These colored tesserae, a contrast to the dull sea of roof tiles below. A train rattles in the distance and then Rapallo fades from my memory. At the heart of this exciting debut collection is the impulse to explore: family history in Europe, migration to Australia, the contours of memory and desire. Exquisite lyric and deft narrative illuminate history's mosaics and brilliant shards of lost time.